1972
DOI: 10.1104/pp.49.4.467
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction and Oxidation of Cytochrome f in Bundle Sheath Cells of Maize

Abstract: The photo-oxidation of cytochrome f (cytochrome c,54) in bundle sheath cells isolated from leaves of maize (Zea mays var. DS 606A) has been compared with that in intact maize leaf and in isolated pea leaf cells (Pisum sativum L.). In all cases, illumination with red light caused a negative absorbance change at 554 nm which was attributed to the oxidation of cytochrome /. The extent of this change was greater using monochromatic red light at wavelengths above 700 nm compared with wavelengths below 700 nm. 3-(3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1972
1972
2006
2006

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…However, only an increased oxidation level was observed in cells illuminated with either 701 nm light or treated with DCMU and illuminated with any one of the three selected wavelengths. These experiments and those with autotrophic ceils of Scenedesmus are in good agreement with those reported earlier (Bishop et al 1972).…”
Section: Photooxidation Of Cytochrome Fsupporting
confidence: 93%
See 1 more Smart Citation
“…However, only an increased oxidation level was observed in cells illuminated with either 701 nm light or treated with DCMU and illuminated with any one of the three selected wavelengths. These experiments and those with autotrophic ceils of Scenedesmus are in good agreement with those reported earlier (Bishop et al 1972).…”
Section: Photooxidation Of Cytochrome Fsupporting
confidence: 93%
“…Since Cyt/is oxidized by photosystem I and reduced by photosystem II its redox kinetics will provide more information about the potency of the two photosystems. Bishop et al (1972), reported for isolated leaf cells that light above 700 nm, activating mainly photosystem 1, caused a very rapid and complete oxidation of Cyt / Since photosystem II could not produce sufficient reductants under these conditions, the dark reversal of the oxidized Cyt/was slowed down. On the other hand, wavelengths below 700 nm cause a comparatively lower oxidation level of Cyt / but produce more reductants for its dark reversal.…”
Section: Photooxidation Of Cytochrome Fmentioning
confidence: 99%
“…The independence of the photo-oxidation of cytochrome f from wavelength shown by bundle sheath chloroplast preparations has been interpreted as evidence of the inactivity of photosystem 11 (19), but could also be due to reductants produced in photosystem II being unavailable to photosystem I. The question of whether photosystems I and II are linked for electron flow in intact bundle sheath cells is considered in an accompanying paper (4).…”
Section: Discussionmentioning
confidence: 99%
“…PSII activity did not disappear indicating that loss of the ability to photoreduce NADP + was due to unlinking of the photosystems. Bishop et al (1972) also suggest that in BS chloroplasts of maize, PSII is not disappearing but rather that two photosystems are becoming disconnected. No Hill reaction activity in BS chloroplasts of maize was also found by Ku et al (1974) with ferricyanide or DCPIP as the Hill oxidant.…”
Section: Zea Maysmentioning
confidence: 93%